Use of Decellularized Human Skin to Repair Esophageal Anastomotic Leak in Humans - Bozuk, Michael I. (Society of Laparoendoscopic Surgeons, 2006)
Multiple surgical techniques have been described for repair of esophageal leaks. None of the repairs are optimal, and the morbidity and mortality of an esophageal leak remains high. To our knowledge, this is the first case report of use of AlloDerm (Lifecell Corp, Brachburg, NJ) to successfully repair a thoracic anastomotic esophageal leak.